KNOWLEDGE, ATTITUDE AND PRACTICES OF MALARIA PREVENTION AMONG PREGNANT WOMEN ATTENDING ANTENATAL CLINIC AT GOMA HEALTH CENTER III, MUKONO DISTRICT: A CROSS SECTIONAL STUDY. - Mutesi , Hope Pauline; Turumanya , Judah; Otile, Samuel (Student’s Journal of Health Research Africa, 2024)
Objectives To determine the level of knowledge, attitude and practices about malaria prevention among the pregnant women attending antenatal clinic at Goma Health center III. Methodology: The study was a descriptive cross-sectional study that involved the use of quantitative approach of data collection and analysis. Consent from 145 pregnant women attending antenatal clinic at Goma Health center III was sought before participation into the study, they answered questions in the questionnaires in line with the study objectives and the results data was stored in Microsoft excel and analysed using stara version 14.0. Results Out of the 145 pregnant women who participated, 87 of them (60%) were aged between 21-40 years, and only a few were aged 45 years and above. All of them had heard about malaria in pregnancy whereby most of them (98, 67.58%) had heard about it from health facilities. They all believed that mosquitoes were the Vectors that spread malaria, but a few were ignorant about its transmission where 6 (4.13%) believed it was transmitted by coming into contact with a malaria patient, other 6 (4.13%) by eating contaminated food, some 2 (1.37%) believed in transmission by eating so many mangoes. Conclusion The participants ‘basic knowledge about malaria in pregnancy was good because all of them (100%) had heard about it and most of them knew its correct transmission, signs and symptoms, and prevention measures. Their attitudes towards malaria prevention were not so good because most of them strongly agreed that the disease is serious and life-threatening, their practices towards malaria prevention were good. Recommendations The researcher therefore recommends that more health education should be done about malaria transmission to ensure excellent knowledge, self-medication should be strongly condemned because most Africans believe in it but it is risky to pregnant women.